Hypoxia: Friend or Foe for drug delivery in Pancreatic Cancer. (1st November 2020) - Shah, Vidhi M.; Sheppard, Brett C.; Sears, Rosalie C.; Alani, Adam WG.
Abstract: Pancreatic ductal adenocarcinoma (PDAC) remains one of the most lethal solid tumors with an overall five-year survival rate of that has only just reached 10%. The tumor microenvironment of PDAC is characterized by desmoplasia, which consist of dense stroma of fibroblasts and inflammatory cells, resulting in a hypoxic environment due to limited oxygen diffusion through the tumor. Hypoxia contributes to the aggressive tumor biology by promoting tumor progression, malignancy, and promoting resistance to conventional and targeted therapeutic agents. In depth research in the area has identified that hypoxia modulates the tumor biology through hypoxia inducible factors (HIFs), which not only are the key determinant of pancreatic malignancy but also an important target for therapy. In this review, we summarize the recent advances in understanding hypoxia driven phenotypes, which are responsible for the highly aggressive and metastatic characteristics of pancreatic cancer, and how hypoxia can be exploited as a target for drug delivery.